IJON DALAM JARINGAN PERDAGANGAN ANAK PEREMPUAN YANG DILACURKAN - Johanna Debora Imelda (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2006)
This paper explores the mechanism of the ijon system in child trafficking and the actors involved in this network. The focus is on the girls who sell tea in bottles in Jakarta. The bossess in child trafficking using the ijon system to maintain their product (the girl child). They keep the girls under endless debt (either money or moral obligation) eversince their leaved their origin place. The actors involved in maintaining this system are the girls' parents and relatives, the bossess in Jakarta and mediators in their origin place, and the local elites in the village. Ironically, the girls who involved in this network were not aware of the exploitation they are going through. On the other side, which the fact happened, they were exploited economically, physically, psychologically, and sexually.